Design Analysis of a Disabled Tricycle Electric Bike Frame Using Finite Element Analysis (Fea) - Pratama, Hidayat; Hilmy, Fuad; Sulistiyo, Raka Mahendra; Salahudin, Xander (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
Mobilization is very important to meet the needs that require someone to move or travel, especially for the disabled. One solution to help the disabled is to design flexible and safe vehicles for them. To find out whether the design is safe or not is by simulation Finite Element Analysis (FEA). This study was conducted to analyze three designs of electric bicycle frames for the disabled made using Solidworks software which is then simulated using Ansys Workbench software which produces output in the form of valuesvon mises stress, deformation, and safety factor. The selection of this design is based on simulation results which show that the von mises stress obtained was 62,669 MPa, its maximum deformation value of 0.32879 mm, and safety factor obtained a value of 6.6221. This simulation uses a load of 80 kg and there is an additional battery at the bottom weighing 10 kg. The simulation results show that design 3 provides the best performance, this is because the design obtains safety factor highest.